Pelatihan Pembuatan Video Konten untuk Membangun Personal Branding di Media Sosial bagi Karang Taruna Kecamatan Margadana Kota Tegal - Nugroho Adhi Santoso; Sari Surorejo; Pinky Septisiana Ananda; Bintang Nusantara (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
The training activity of creating video content to build personal branding on social media for Karang Taruna (Youth Organization) in Margadana District, Tegal City is a strategic effort to increase the capacity and creativity of the younger generation in the digital era. This training is motivated by the rapid development of information technology and social media, which makes the ability to manage self-image or personal branding a crucial aspect in developing the potential of individuals and organizations. Through this activity, Karang Taruna members are given an understanding of the basic concepts of personal branding, strategies for building a positive digital identity, as well as technical skills in designing and producing engaging, educational video content that suits the character of each participant. In addition to theory, participants are also trained practically in the video creation process from planning ideas, shooting, to editing using simple software. It is hoped that through this training, Karang Taruna youth will be able to utilize social media productively as a platform for promoting social activities, developing self-potential, and spreading positive values in the community. This activity also serves as a means to strengthen the existence of Karang Taruna as a youth organization that is adaptive to technological advances and plays an active role in building a positive image of the younger generation at the local and global levels. Thus, this training not only provides technical skills, but also forms a creative, innovative, and responsible mindset in the use of digital media.